Effect Of Using Quantitative Methods Of Demand Forecasting In Improving Of Supply Chain Performance:" Case Study In One Of An Industerial Organization" - سعيد, اصفاد مرتضى; عكلة, اخلاص ستار (Journal of Economics and Administrative Sciences, 2024)
Objecte The study aims to test the effect of using the appropriate quantitative method of demand forecasting in improving the performance of supply chain of the aviation fuel product ( The study sample), One of the products of the Doura refinery (The study site), By testing a set of quantitative methods of demand forecasting using forecasting error measurements, and choosing the least faulty, most accurate and reliable method and adept it in the building  chain.Is the study of problem through a starting with the following main questions:"Does the chosen of the appropriate quantitative method for demand forecasting affect the performance of supply chain of the aviation fuel product in the refinery (site the study)?"The importance of study shows through investment all opportunities sales and reduce the opportunitiesAdopted the study used the case study methodology to study the methods used in the Refinery to demand forecast for aviation fuel and analyze the supply chain, of the product  then test a set of quantitative methods to forecast  the demand of the sample of the study and choose the best method using predictive error measurements, to  depending it in the building  of supply chain proposed by the study, And then compare the performance of the current and proposed chain using a set of financial and quantitative measures most important (quantity of production, quantity of shortage deficit, total costs, revenues, profits) .The study reached a set of conclusions the light of results the most important that the measurements adopted in the comparison of the two chain have indicated that the supply chain proposed by the study the current excelled supply chain of aviation fuel.